(untitled) (Scientific journal of the Fergana State University, 2024)
In addition to political, social, economic and other factors, geographical factors also play an important role in the historical development of any society. In recent years, the increasing anthropogenic pressure on the development trends of the world community and the economy, on natural complexes and geosystems, increases the relevance of studying the role of the geographical factor in the development of society. This article focuses on the role of geographical factors in formation the culture of water use on a global scale.